2018
DOI: 10.1055/s-0038-1669470
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Administration Alters Hepatic Blood Flow Across Age: Systematic Review of Animal Experimental Studies

Abstract: Testosterone levels decline gradually with advancing age. At this point, testosterone administration as a therapy has been largely used to improve different outcomes. However, testosterone induces dose-dependent negative effects on the structure and function of the liver across age. Therefore, the present study aimed to carry out a systematic review of the effects of testosterone administration on the hepatic structure of adult and aged animals. We have searched the PubMed, Google Scholar, Science Direct, Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…High blood pressure is associated with a three to four fold increase in the risk of stroke, fibrillation, and ventricular arrhythmia. 10,11 This study corroborates the results found Seara et al 15 , showing a significant increase in myocardial thickness and ventricular cavity diameter, in male mices.…”
Section: Discussionsupporting
confidence: 91%
“…High blood pressure is associated with a three to four fold increase in the risk of stroke, fibrillation, and ventricular arrhythmia. 10,11 This study corroborates the results found Seara et al 15 , showing a significant increase in myocardial thickness and ventricular cavity diameter, in male mices.…”
Section: Discussionsupporting
confidence: 91%